Increased oxygen extraction and mitochondrial protein expression after small muscle mass endurance training - Skattebo, Ø.; Capelli, C.; Rud, B.; Auensen, M.; Calbet, J. A. L.; Hallén, J. (Scandinavian Journal of Medicine & Science in Sports, 2020)
When exercising with a small muscle mass, the mass-specific O2 delivery exceeds the muscle oxidative capacity resulting in a lower O2 extraction compared with whole-body exercise. We elevated the muscle oxidative capacity and tested its impact on O2 extraction during small muscle mass exercise. Nine individuals conducted six weeks of one-legged knee extension (1L-KE) endurance training. After training, the trained leg (TL) displayed 45% higher citrate synthase and COX-IV protein content in vastus lateralis and 15%-22% higher pulmonary oxygen uptake (VO2peak) and peak power output (WO2peak) during 1L-KE than the control leg (CON; all P < .05). Leg O2 extraction (catheters) and blood flow (ultrasound Doppler) were measured while both legs exercised simultaneously during 2L-KE at the same submaximal power outputs (real-time feedback-controlled). TL displayed higher O2 extraction than CON (main effect: 1.7 ± 1.6% points; P = .010; 40%-83% of WO2peak) with the largest between-leg difference at 83% of WO2peak (O2 extraction: 3.2 ± 2.2% points; arteriovenous O2 difference: 7.1 ± 4.8 mL· L-1; P < .001). At 83% of WO2peak, muscle O2 conductance (DMO2; Fick law of diffusion) and the equilibration index Y were higher in TL (P < .01), indicating reduced diffusion limitations. The between-leg difference in O2 extraction correlated with the between-leg ratio of citrate synthase and COX-IV (r = .72-.73; P = .03), but not with the difference in the capillary-to-fiber ratio (P = .965). In conclusion, endurance training improves O2 extraction during small muscle mass exercise by elevating the muscle oxidative capacity and the recruitment of DMO2, especially evident during high-intensity exercise exploiting a larger fraction of the muscle oxidative capacity.